2021
DOI: 10.3390/ani11020419
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study on Lameness Recovery in 10 Dogs Affected by Iliopsoas Injury and Submitted to a Physiotherapeutic Approach

Abstract: This preliminary study has investigated the outcome of physiotherapy in 10 dogs affected by a primary lesion of the iliopsoas muscle and the potential effects of sex, age, and breed on recovery. Ten dogs with primary injury of the iliopsoas muscle were retrospectively included in this study. Dogs were submitted to a rehabilitation program, characterized by a multimodal approach, including physical therapies and modalities. After recovery, patients were submitted to a further support period of rehabilitation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…One study evaluated musculoskeletal ultrasound in agility dogs with iliopsoas injury and reported evidence of both acute and chronic inflammation within the same patient in 62.8% of cases, consistent with repeat micro-injury (5). With regards to iliopsoas injury recovery, this survey found that 56% of dogs were able to return to competition within 3 months, consistent with a median of 91 days to full recovery reported by Spinella et al (9). The remainder of dogs had a more prolonged convalescence, with 24% returning in 4-6 months, 14% being out of agility for longer than 6 months, and 6% officially retiring.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…One study evaluated musculoskeletal ultrasound in agility dogs with iliopsoas injury and reported evidence of both acute and chronic inflammation within the same patient in 62.8% of cases, consistent with repeat micro-injury (5). With regards to iliopsoas injury recovery, this survey found that 56% of dogs were able to return to competition within 3 months, consistent with a median of 91 days to full recovery reported by Spinella et al (9). The remainder of dogs had a more prolonged convalescence, with 24% returning in 4-6 months, 14% being out of agility for longer than 6 months, and 6% officially retiring.…”
Section: Discussionsupporting
confidence: 79%
“…The iliopsoas muscle is formed by the psoas and iliacus muscles and acts as an important flexor and stabilizer of the hip and vertebral column (8). The iliopsoas is prone to acute injury and strain when there is stretch while in eccentric contraction, which is common with a slip or fall, mis-jumping, or quick changes in direction (5,8,9). As with any muscle injury, if left undiagnosed or untreated these initial injuries can progress to become chronic in nature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations